Transcriptome reprogramming, epigenetic modifications and alternative splicing orchestrate the tomato root response to the beneficial fungus Trichoderma harzianum - De Palma, Monica; Salzano, Maria; Villano, Clizia; Aversano, Riccardo; Lorito, Matteo; Ruocco, Michelina; Docimo, Teresa; Piccinelli, Anna Lisa; D’Agostino, Nunzio; Tucci, Marina (Horticulture research, 2019)
Beneficial interactions of rhizosphere microorganisms are widely exploited for plant biofertilization and mitigation of biotic and abiotic constraints. To provide new insights into the onset of the roots–beneficial microorganisms interplay, we characterised the transcriptomes expressed in tomato roots at 24, 48 and 72 h post inoculation with the beneficial fungus Trichoderma harzianum T22 and analysed the epigenetic and post-trascriptional regulation mechanisms. We detected 1243 tomato transcripts that were differentially expressed between Trichoderma -interacting and control roots and 83 T. harzianum transcripts that were differentially expressed between the three experimental time points. Interaction with Trichoderma triggered a transcriptional response mainly ascribable to signal recognition and transduction, stress response, transcriptional regulation and transport. In tomato roots, salicylic acid, and not jasmonate, appears to have a prominent role in orchestrating the interplay with this beneficial strain. Differential regulation of many nutrient transporter genes indicated a strong effect on plant nutrition processes, which, together with the possible modifications in root architecture triggered by ethylene/indole-3-acetic acid signalling at 72 h post inoculation may concur to the well-described growth-promotion ability of this strain. Alongside, T. harzianum -induced defence priming and stress tolerance may be mediated by the induction of reactive oxygen species, detoxification and defence genes. A deeper insight into gene expression and regulation control provided first evidences for the involvement of cytosine methylation and alternative splicing mechanisms in the plant– Trichoderma interaction. A model is proposed that integrates the plant transcriptomic responses in the roots, where interaction between the plant and beneficial rhizosphere microorganisms occurs. Symbiosis: the genetics of beneficial tomato root–fungus interaction The fungus Trichoderma harzianum induces differentiated protein production in tomato roots that benefits plant nutrition and survivability. Microorganisms advantageous to plants have long been exploited in agriculture; however, with limited studies into the interface of Trichoderma fungus and plants—the roots. Italian researchers, led by the Research Centre for Vegetable and Ornamental Crops' Nunzio D'Agostino and the National Research Council’s Marina Tucci, inoculated tomato plant roots with T. harzianum over 72 h, finding over 1200 examples of differential gene expression and post-expression modification that resulted in improved plant growth and immune system regulation. The interaction also induces a root change that likely promotes further interaction with the fungus and increased stress tolerance via promoting antioxidation and defensive activity. The team’s work provides early evidence of the molecular mechanisms behind root–fungus symbiosis and may help to inform crop breeding and fertilisation strategies.